1977
DOI: 10.1017/s031716710002521x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cyclic Nucleotides in the CNS

Abstract: SUMMARY:On the basis of the information presented in this review, it is difficult to reach any firm decision regarding the role of cyclic AMP (or cyclic GMP) in synaptic transmission in the brain. While it is clear that cyclic nucleotide levels can be altered by the exposure of neural tissues to various neurotransmitters, it would be premature to claim that these nucleotides are, or are not, essential to the transmission process in the pre- or postsynaptic components of the synapse. In future experiments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1979
1979
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(30 citation statements)
references
References 328 publications
(323 reference statements)
0
29
0
1
Order By: Relevance
“…This nucleotide is normally a constituent of central nervous system tissue (9) and increased amounts are found in the cerebrospinal fluid of patients with brain disease (8). Cyclic GMP is relatively stable and the radioimmunoassay method for its detection (10) is simple and rapid.…”
mentioning
confidence: 99%
“…This nucleotide is normally a constituent of central nervous system tissue (9) and increased amounts are found in the cerebrospinal fluid of patients with brain disease (8). Cyclic GMP is relatively stable and the radioimmunoassay method for its detection (10) is simple and rapid.…”
mentioning
confidence: 99%
“…It has been reported that adenosine may have a modulatory effect on transmembrane Cat+ fluxes (Phillis 1977) and it may suppress Caf + influx into intracellular compartments (Ten Bruggencate et al 1977). If such a depression of Ca++ flux occurs in presynaptic sites, it may reduce the release of brain neurotransmitters (Schubert et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nomura et al (1984) found significantly lower basal activity in the brain of aged compared to adult rats. Interestingly, Dewar et al (1990) Several neurotransmitters are well known to stimulate the formation of cyclic-AMP by activation of adenylate cyclase (Phillis, 1977). Cyclic-AMP plays a role in expression or activation of ion channels and acetylcholine receptors (Artalejo et al, 1990;Ifune and Steinbach, 1990).…”
Section: H]forskolin Bindingmentioning
confidence: 99%